YouTube as a Financial Literacy Media for the Millennial Generation - Muzzamil, Zafira Andini; Ayuningtyas, Fitria; Muqsith, Munadhil Abdul (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research explains how YouTube has become a financial literacy medium for the millennial generation. The current technological era has made YouTube a video-based social media platform popular with many groups because it is considered more interactive and shows more real phenomena, providing more detailed and extensive information. This makes YouTube the most widely used social media in 2019. Various information is available on YouTube which is content from users who have YouTube channels. One piece of information that is widely spread is information about financial literacy. Financial literacy is considered important for the millennial generation to understand as a generation belonging to a productive group that influences economic activities to be wiser in consumption activities. The millennial generation is considered to have problems with financial issues because they have an extravagant, consumptive lifestyle driven by information from the media and technology. This research discusses YouTube content that can be used as a financial literacy medium for the millennial generation using literature study research methods and taking data sources from three YouTube channels in Indonesia. The results of this research show that YouTube can be used as social media that provides financial literacy information and has an influence on financial understanding for the millennial generation in the digital space.